(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: Internet disruption has unprecedentedly made social media a global village and global digital market where business and customers interacts boundlessly. People’s interaction has far gone beyond boundary and businesses are seeing and harnessing these opportunities. Objective: This study investigated the effect of social media influencers on purchase intention among social media users. Method: The population of this study consist of active social media users in Anambra state. Sample size of 220 was arrived at using convenience sampling for infinite population. Reliability and validity test were done through construct Reliability and Discriminant validity respectively through smart- pls. Data was computed with SPSS version 24 and analysed with SEM via Smart-Pls. Result: The finding of this investigation showed that trustworthiness, attractiveness and influencer product match up has positive and significant effect on purchase intention respectively. Conclusion: More so, expertise does not influence purchase intentions. Finally, if there is need social media influencer, organizations should painstakingly seek influencers with high trust level among audience, highly attractive and it’s congruity with the intended promoted product.